Bioethical Threads in the Reflection of Tibetan Refugees in India - Lisiecki, Marcin (2021)
This article aims to trace and describe the bioethical threads in medical practice and the understanding of medicine among Tibetan refugees living in India. Taking up such a task results mainly from the fact that only traces of bioethical reflection are visible in Tibetan society, but without the awareness that it requires systematic reflection on its essence and changes that accompany modern medicine. I define the state of the discussion on Tibetan bioethics as preparadigmatic, i.e., one that precedes the recognition of the importance of bioethics and the elaboration of its basic concepts. In this paper, I will show how the Tibetan refugees today, in an unconscious way, approach bioethics, using the example of life-related topics, namely beginning and death. To this end, I chose topics such as abortion, fetal sex reassignment, euthanasia, and suicide. On this basis, I will indicate the main reasons that hinder the emergence of bioethics and those that may contribute to systematic discussions in the future. An introduction to Tibetan medicine will precede these considerations. I will show how medical traditions, especially the Rgyud bzhi text, are related to Tibetan Buddhism and opinions of the 14th Dalai Lama.
Keywords: Dalai Lama; rgyud bzhi; Tibet; Tibetan Buddhism; Tibetan Medicine; Abortion; Bioethics; Book; Death; Euthanasia; Fetus; Health; Pain; Patient; Suicide